COMPREHENSIVE STUDY OF GASDYNAMIC FEATURES OF JETS OUTFLOW FROM NOZZLES OF CYLINDRICAL DESIGN FOR OXYGEN CONVERTERS CONDITIONS (Modern Problems of Metallurgy, 2025)
The oxygen converter process is the only competitive leader in the production of liquid steel. This is primarily due to the available different types of blowing devices that perform various functions during smelting and allow for rapid adaptation to changing technological conditions. The main types of nozzles for top blowing devices are Laval nozzles, which are used to supply the main oxygen flow, and cylindrical nozzles, which are more often used for postcombustion of exhaust gases. The results of a multifaceted study of the features of the gas jet outflow from the cylindrical nozzle are presented to clarify the rational limits of their use in the design of the top blown lances of an oxygen converter. It was conducted by shadow shooting methods when the gas stream flows into the free air environment and into a model liquid - water, and by mathematical modeling methods. In accordance with the industrial technological conditions of using nozzles, it was established that when the height of the cylindrical nozzles was 40 calibers from the surface of the calm bath, high indicators of the energy of the blowout gas and, accordingly, the gas flow velocities were achieved when the blowing gas was supplied with an excess pressure of at least 300 kPa. At the same time, the possibility of penetration into a real slag-metal melt under such conditions (when extrapolating calculations to a 60 kg laboratory model of an oxygen converter) was at the level of 56 - 65% of the height of the slag melt. It was noted that to increase the permeability of the gas jet flowing from the cylindrical nozzle, it is necessary to reduce the lance height by 25%relative. The characteristic features of the change in the shape of the gas jet and the distribution of velocities along the length when the pressure of the blowing gas changes, and their influence on the actual depth of immersion of the gas jet in the model liquid - water, were noted. A conclusion was made about the feasibility of using cylindrical nozzles as second-row nozzles for multi-row upper lances.
Keywords: top blowing; cylindrical nozzle; gas jet; shadow shooting; mathematical modeling; immersion depth.